Da Baleia ao Urso Branco nos caminhos de Bananeiras: Uma investigação sobre os reguladores do tempo na Educação Infantil - Catão, Maria José Duarte (2009)
The human being uses calendars, address books, watches, and alarm clocks in order to guide and harmonize the daily activities as well as the relations with other subjects. The expression time regulators appears in this research as a tool which will enable how the temporal notion is experimented in school producing, thus, subjectivity. The used theoretical and methodological foundation aimed to visualize the diversity. This reason justifies a closer look at W. Benjamin, M. Foucault and F. Guattari whose reflections break up the linear and homogenous time perception, viewing a temporality based on the concrete experiences of the individuals. As concerns the daily routine of the Infantile Education School O Grãozinho , by means of interviews and observations from field registers, time regulators were found. These discipline and schedule the daily activities, promoting the breakup between the pedagogical activity and the recreation based on time linearity. Such regulators are present in the Baleia , a school transport which informs the entrance and exit time; in the routine which standardizes the action, in the infantile literature; in headlines with dates; rules referring to the infantile growth time line; songs, etc. Children are initiated by the use of these time regulators earlier and earlier, but it is possible that, in the daily routine, they do find ways to skip them, making bifurcations potential.